EFFECTIVENESS OF THEORY OF MIND THERAPY CARRIED OUT BY PARENTS OF CHILDREN WITH AUTISM – A PRELIMINARY STUDY - Mącik, Dorota; Kowalska-Dąbrowska, Monika; Pietraszak, Malwina (Studia Psychologica: Theoria et praxis, 2017)
The subject of the paper is therapy program for children with autism which is applicable for parents who can use it in everyday situations. Therapy is focused on the Theory of Mind Mechanism (ToMM), mainly recognizing others’ mental states, emotions and true or false beliefs. 12 children (8–12 yr olds) with autism was divided into 2 groups: 6 participated in individual sessions (parents repeated sessions activities at home) by 6 months, the next 6 made the control group without treatment. Session plan is described. There is a large effect size in treatment group. The most increased skills were: distinguishing previous from present opinions, taking others’ perspective and emotion recognizing. Statistical analysis and qualitative interpretation confirm therapy effectiveness.